Готовность к подвигу: слагаемые и истоки - Ширман Александр Александрович (Присягаем Отечеству, 1988)
Экземпляры: КХ (20101208) / Инвентарный номер: 0281337 / Цена: 0.20 / Сис.шифр: 68 / Авт.знак: Ш 64 / ГРНТИ: 78 / ББК: 68.491